Myocardial Fatty Acid-Glucose Fuel Balance as Target to Treat Cardiac Diseases - Glatz, Jan FC; Nabben, Miranda; Luiken, Joost JFP (Cardiology and Cardiovascular Medicine, 2020)
The currently most prevalent cardiac diseases, diabetic cardiomyopathy and hypertrophic heart failure, each associate with a chronic change in energy substrate utilization towards a single type of substrate, i.e., fatty acids or glucose, respectively. Recent experimental studies suggest that proper cardiac contractile performance is dependent on a finely tuned balance between the utilization of these two substrates. Furthermore, re-balancing myocardial fuel supply (fatty acids versus glucose) appears an effective treatment option in cardiac disease.